Hypertransaminasemia in celiac disease: Celiac or autoimmune hepatitis? - Eliseu,Liliana (2013)
The authors report the case of a young woman presenting with asymptomatic hypertransaminasemia whose etiologic investigation led to the diagnosis of celiac disease. The concomitant existence of antinuclear and anti-smooth muscle antibodies and of elevated sérum immunoglobulin G concentrations raised the hypothesis of autoimmune hepatitis, reason for performing a liver biopsy. The final diagnosis was celiac hepatitis, resolved with dietary treatment alone. Celiac disease is a systemic disorder primarily affecting the small bowel. A variety of liver manifestations have been described and there is an established association with autoimmune hepatic disorders. Isolated elevation of aminotransferases is the most common hepatic presentation, usually reversible with gluten avoidance. Although rarely necessary, liver biopsy may be crucial in selected cases.